Tacrine-NO donor and tacrine-ferulic acid hybrid molecules as new anti-Alzheimer agents: hepatotoxicity and influence on the cytochrome P450 system in comparison to tacrine - Amelie, Lupp; Dorothea, Appenroth; Lei, Fang; Michael, Decker; Jochen, Lehmann; Christian, Fleck (Arzneimittelforschung, 2010)
Tacrine (CAS 321-64-2) is a reversible acetylcholine esterase inhibitor that, despite exerting beneficial effects on Alzheimer’s disease (AD), displays marked hepatotoxicity. Searching for safer drugs and taking into account the multi-patho-genesis of AD, two tacrine-NO donor hybrid molecules (FL16, FL38) as well as a tacrine-ferulic acid hybrid (FL67) were synthesized. NO donors coupled to the tacrine moiety may exert an additional beneficial effect on AD via an increased blood supply to the brain and by reducing inflammation. Ferulic acid is an antioxidant.To investigate the hepatotoxicity and effects on the cytochrome P450 (CYP) system of the liver, female rats were treated with the highest tolerated dose of tacrine or equimolar doses of the novel compounds 24 or 36 h, respectively, before sacrifice.Tacrine caused pericentral necrosis and fatty degeneration of the hepato-cytes, loss of liver glycogen and (indicating oxidative stress) induction of heme oxygenase (HO)-l. No histopathological changes were observed with the hybrids, but a glycogen deficit and an elevation of HO-1 was noticed after FL38 or FL67 treatment. Both tacrine and the hybrids, but mainly FL38 and FL67, caused an induction of CYP1A1, 2B1 and 3A2 expression. CYP activity was noticeably increased after treatment with FL38 and FL67 only.Thus, since it displays much less hepatotoxicity and interaction potential at the CYP system than tacrine and the other hybrids, FL16 is a good candidate for further investigations.
Keywords: Anti-Alzheimer agents; CAS 321-64-2; Cytochrome P450; Ferulic acid; NO-donors; Tacrine, hepatotoxicity, hybrid molecules